2002
DOI: 10.1002/j.0022-0337.2002.66.9.tb03569.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Stress and Psychological Disturbance Among Dental Students in the West Indies

Abstract: The aim of this study was to investigate sources of stress and psychological disturbance in dental students across the five years of undergraduate study at a dental school in Trinidad. Eighty-three percent of students completed a modified version of the Dental Environment Stress questionnaire (DES) and the Brief Symptom Inventory (BSI). On a scale ranging from 0 (not stressful) to 5 (highly stressful), overall mean DES scores for each of the five years of study were 1.58, 1.83, 2.65, 2.39, and 2.61 respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
143
6
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 15 publications
27
143
6
9
Order By: Relevance
“…This finding is inconsistent with that from other studies of DS which have looked at DES individual item stressors across each year of study and found that Year 3 DS reported the same transition as being highly stressful. 5,32 Unlike some dental undergraduate programmes, that focus on theory and laboratorybased skills education in the first two years, the UPDA curriculum introduces clinical experience at a very early stage in Year 1 (after 3 months), which may have been a contributing factor which lessened the perceived stress of transition to practice for the studied DHDTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with that from other studies of DS which have looked at DES individual item stressors across each year of study and found that Year 3 DS reported the same transition as being highly stressful. 5,32 Unlike some dental undergraduate programmes, that focus on theory and laboratorybased skills education in the first two years, the UPDA curriculum introduces clinical experience at a very early stage in Year 1 (after 3 months), which may have been a contributing factor which lessened the perceived stress of transition to practice for the studied DHDTS.…”
Section: Discussionmentioning
confidence: 99%
“…Committee, and an anonymous, self-reported online questionnaire ( Figure 1 The DES 31 was chosen as it is the most widely used measurement in the dental setting, within the existing literature. A modified version was used, 32 consisting of thirty-nine items describing stressors specifically relating to dental undergraduate training. The response to each item was rated on a five-point scale: 0 = not pertinent, 1 = not stressful, 2 = slightly stressful, 3 = moderately stressful and 4 = very stressful.…”
Section: Ethical Approval Was Gained From the University Of Portsmoutmentioning
confidence: 99%
“…Family responsibilities and duties of married dental students, as well as having children, increase psychological pressure and affecting the overall amount of stress. As revealed by other studies, married students are expected to reside in their own homes and live away from parents' home (34)(35)(36).…”
Section: Discussionmentioning
confidence: 93%
“…If a student fails his or her exams, he or she will not pass their courses, will have to face their parents and professors after a failing grade, and may have subsequent personal problems (daily life factor), as described by Yap et al 40 Furthermore, the atmosphere in the clinic item is essential to distinguishing the first period from the second, and reflects the transition from basic sciences to clinical sciences. 47 The fact that the responsibilities associated with patient management scored higher in our sample than the opinions that patients may have regarding the treatments received suggests that what actually causes stress among dental students is carrying out treatments, not The primary obstacle we encountered during this study was the potential subjective nature of the responses given. In order to validate the tools applied here, we suggest carrying out a multicentric study in all of the dental schools in the Dominican Republic.…”
mentioning
confidence: 81%
“…Yet we can affirm that the academic factor is the most relevant stressor, as reflected in other studies. 22,35,40,41,47,48 That being said, this factor is not exclusive, as it interacts with others. If a student fails his or her exams, he or she will not pass their courses, will have to face their parents and professors after a failing grade, and may have subsequent personal problems (daily life factor), as described by Yap et al 40 Furthermore, the atmosphere in the clinic item is essential to distinguishing the first period from the second, and reflects the transition from basic sciences to clinical sciences.…”
mentioning
confidence: 99%